2012
DOI: 10.2466/05.23.25.pms.114.1.174-184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Verbal Cueing on Trajectory Anticipation in the Penalty Kick among Novice Football Goalkeepers

Abstract: The effect of a cueing technique on novice goalkeepers' anticipation of trajectory in penalty kicks was investigated. 28 novice football goalkeepers from junior teams were randomly selected and divided into experimental (n = 14) and control (n = 14) groups. Following a pre-test, participants performed 30 trials of a simulated penalty-kicking task in a spatially occluded condition. They were required to react to penalty kicks and were informed of their performance in anticipating the direction in which the ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Participants who received verbal cues improved their reaction time and decision accuracy, whereas a physical practice group did not; similar results were reported by Williams and colleagues [ 52 ]. Verbal instructions may also improve novice football goalkeepers’ anticipation skill [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants who received verbal cues improved their reaction time and decision accuracy, whereas a physical practice group did not; similar results were reported by Williams and colleagues [ 52 ]. Verbal instructions may also improve novice football goalkeepers’ anticipation skill [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…In sport, verbal cueing paradigms have typically comprised explicit verbal instruction and rules, designed to increase participants’ knowledge and understanding of relevant aspects of the task [ 51 , 53 ]. However, high levels of cognitive processing and explicit knowledge of a skill can hinder performance, leading to skill breakdown [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three of the four acute studies (75%) showed significant improvements in anticipation or decision-making skills performance in the VBT group at post-test than at pre-test (Poulter et al, 2005;Javier Nunez et al, 2010;Shafizadeh and Platt, 2012). One study that included the NVBT group showed that the VBT group outperformed the NVBT group in anticipation or decision-making skills at post-test (Javier Nunez et al, 2010).…”
Section: Acute Studiesmentioning
confidence: 99%
“…We reviewed ten studies, including six longitudinal studies (Gabbett et al, 2008;Savelsbergh et al, 2010;Ryu et al, 2013;Murgia et al, 2014;Nimmerichter et al, 2016;Fortes et al, 2021) and four acute studies (Poulter et al, 2005;Nunez et al, 2009;Javier Nunez et al, 2010;Shafizadeh and Platt, 2012). Of these, five studies assessed the effects of VBT on elite skill performance (Gabbett et al, 2008;Javier Nunez et al, 2010;Murgia et al, 2014;Nimmerichter et al, 2016;Fortes et al, 2021), four studies investigated the effects on novice skill performance (Poulter et al, 2005;Savelsbergh et al, 2010;Shafizadeh and Platt, 2012;Ryu et al, 2013), and one study examined both elite and novice athletes (Nunez et al, 2009).…”
Section: Video-based Training To Develop the Effectiveness Of Anticip...mentioning
confidence: 99%
“…Research regarding anticipation has been conducted in various sports and situations. 1,2 Studies have been completed regarding anticipation in soccer for goalkeepers right before the penalty kick 3,4 and free kick, 5 and for defense when offense approaches. [6][7][8] Results of this research indicate that elite and skilled athletes are better able to anticipate the direction of the ball, the type of ball, and the opponent's movement that are less skilled athletes.…”
Section: Introductionmentioning
confidence: 99%